Strategy for Improving Work Readiness Vocational High School Graduate - Holisoh, Iis; Nabhani, Irfan; Aulawi, Hilmi (Jurnal Wacana Ekonomi, 2023)
This article aims to examine the strategies that SMK Insan Mandiri Garut should implement to increase graduates who are ready to work. The method used in this research is a qualitative method, namely a special examination that is different in nature and generally uses a top-down examination. From the results it is known that the Insan Mandiri Garut Vocational School research has not been successful in its implementation pattern. Based on the results of the SWOT analysis, the position of Insan Mandiri Garut Vocational School is in quadrant 1. This means that Insan Mandiri Garut Vocational School has opportunities and strengths so that existing opportunities can be utilized as well as possible by optimizing the strengths they have. The strategy that should be implemented in this condition is a growth-oriented strategy or known as the S-O strategy which includes: (a) Improving the quality of graduates through various academic achievements, competency certification, learning innovation, and establishing partnerships with more bona fide parties. business world; (b) Increasing the commitment/loyalty of teaching and education staff by ensuring their welfare; (c) Organizing a competency-based education and training model by utilizing developments in information and communication technology; and (d) Increasing the quality and quantity of prospective new student recruitment through promotional activities.